Cell growth monitoring in a tetrapolar electrode configuration - Singh Jagbir; Khambete Niranjan D. (Journal of Electrical Bioimpedance)
There are various methods for cell growth monitoring. However, most of these methods have drawbacks, such as being invasive, not providing real-time results, or being costly. In this study, we present an alternate method of cell growth monitoring, which is low-cost, non-invasive, real-time, and uses Electrical Impedance Spectro-scopy (EIS). In this work, commercially available culture plates were fitted with custom tetrapolar electrodes, and mouse cells were cultured on them. The variation of culture media impedance, resulting from cell growth, proliferation and other metabolic activities, was recorded over a period of seven days. The results demonstrated an initial increase in impedance corresponding with the cell growth phase, followed by a decrease during the cell death (apoptosis) phase, as confirmed by microscope images. Overall, the results show that our method to monitor cell growth using tetrapolar electrodes is promising and can be further refined for related applications.